Keanekaragaman Jenis Paku-Pakuan (Pteridophyta) Di Mangrove Muara Sungai Peniti Kecamatan Segedong Kabupaten Pontianak - Riza Linda, Bunia Ceri, Irwan Lovadi (Universitas Tanjungpura, 2014)
Mangrove forest is the habitat of various kinds of organisms, some of which are ferns (Pterydophyta). This study aim was to determine the types of ferns those can be found in mangrove forest of Peniti river estuary. The research was conducted from December 2013 to January 2014 in mangrove forest of Peniti river estuary in Segedong district of Pontianak regency. Cruise method was employed to collect ferns. There were 11 species of fern belonging to Polypodiopsida and 7 families. Acrostichum aureum and A. speciosum are mangrove fern in the area being studied.